Clostridioides difficile proline fermentation in response to commensal clostridia. (June 2020) - Lopez, Christopher A.; McNeely, Tess P.; Nurmakova, Kamila; Beavers, William N.; Skaar, Eric P.
Abstract: Clostridioides difficile colonizes the intestines of susceptible individuals and releases toxins that mediate disease. To replicate and expand in the intestines, C. difficile ferments proline, and this activity is influenced by the availability of proline and trace nutrients. C. difficile must also compete with the commensal microbiota for these limited nutrients. The specific microbes present in the intestines that may shape the ability of C. difficile to benefit from proline fermentation are unknown. In this study we developed a panel of commensal Clostridia to test the hypothesis that the microbiota influences C. difficile growth through proline fermentation. The experimental panel of Clostridia was composed of murine and human isolates that ranged in their capacity to ferment proline in different media. Competition between wild type C. difficile and a mutant strain unable to ferment proline ( prdB :CT) in the presence of these Clostridia revealed that bacteria closely related to Paraclostridium benzoelyticum and Paeniclostridium spp. decreased the benefit to C. difficile provided by proline fermentation. Conversely, Clostridium xylanolyticum drove C. difficile towards an increased reliance on proline fermentation for growth. Overall, the ability of C. difficile to benefit from proline fermentation is contextual and in part dependent on the microbiota. Highlights: How specific microbiota members influence Clostridioides difficile metabolism is largely unknown. Many members of Clostridia encode the potential to ferment proline. The ability of C. difficile to benefit from proline fermentation is influenced by some Clostridia bacteria.